Frequency of methicillin-resistant staphylococcus and antibiogram profile of staphylococcus aureus recovered from different clinical samples - Tariq, Tariq Mahmud; Anwar, Kainat; Iqbal, Mariam Danish; Dogar, Sana Fatima; Saeed, Naureen (International Journal of Pathology, 2024)
Background: Staphylococcus is a ubiquitous bacterium and well-known pathogen causing a variety of infections. The global spread of Methicillin-resistant Staphylococcus aureus (MRSA) constitutes one of the most prevailing challenges to the management of infections caused by this bug. Our objective is to determine the frequency of MRSA and antibiogram profile of S. aureus recovered from different clinical samples.Methods: This cross sectional study was carried out in the Microbiology Laboratory of Shalamar Hospital Lahore. The data of the Staphylococcus isolates including MRSA from pus and swab samples was collected through Electronic Medical Record of the Shalamar Hospital from 1st Jan to 31st Dec 2021. S. aureus was identified by standard protocol including Gram stain, catalase, coagulase, and DNase tests. Antimicrobial susceptibility was carried out by modified Kirby Bauer method. MRSA frequency was determined by the result of sensitivity to cefoxitin.Results: Out of 885 samples submitted for culture, 517 (58.4%) were reported for microbial growth of a known pathogen. The most frequently isolated pathogen was S. aureus (37.9%), followed by E. coli (22.4%), other members of Enterobacteriaceae family (17.8%), Pseudomonas (15.5%), Enterococcus (3.5%), Candida (2.1%), and Streptococcus (0.8%). Amongst S. aureus, MRSA was documented in 46.9% cases. Substantial difference was detected in the susceptibility pattern of Methicillin-sensitive and resistant staphylococci. All staphylococci were resistant to ampicillin while no vancomycin resistance was encountered.Conclusion: MRSA was seen in the local population with a high frequency and they also showed marked resistance against other commonly used antibiotics. Fortunately no vancomycin-resistant S. aureus was reported.